Controls on Primary Productivity in the Eastern Equatorial Pacific, East of the Galapagos Islands, During the Penultimate Deglaciation. Issue 7 (9th July 2020) - Quirós‐Collazos, Lucía; Calvo, Eva; Schouten, Stefan; van der Meer, Marcel T. J.; Rodrigo‐Gámiz, Marta; Pena, Leopoldo D.; Cacho, Isabel; Pelejero, Carles
Abstract: Modern biogeochemical conditions of the Eastern Equatorial Pacific (EEP) region are characterized by high macronutrient concentrations but low phytoplankton abundance due to both iron and silicic acid limitation. Since primary producers significantly impact the global carbon cycle, paleoproductivity in relation to climate change and nutrient availability in this region has been a topic of a number of studies. However, the complex dynamics of this region, especially east of the Galapagos Islands, has led to some discrepancies when linking reconstructed paleoproductivity with potential mechanisms for higher primary productivity. Here we focus on reconstructing primary productivity of haptophyte algae and diatoms, as well as continental material input, sea surface salinity, and sea surface temperature, and compare these reconstructions with existing records for the period comprised between 150 and 110 ka (the penultimate deglaciation period) with the aim to understand the mechanisms that most significantly influence phytoplankton growth over the EEP region east of the Galapagos Islands. Our results suggest enhanced upwelling in the EEP system during the penultimate deglaciation and increased phytoplankton abundance mainly as the result of both the increasing influence of nutrient‐rich Southern Ocean sourced waters through the Equatorial Undercurrent and a higher input of iron through atmospheric deposition. The highest phytoplankton abundances recorded at the study site during the penultimate deglaciation also suggest that maximum input of nutrients might have occurred during the millennial‐scale event Heinrich Event 11 in the North Atlantic as a result of global atmospheric and oceanic reorganizations. Key Points: Primary productivity in the Eastern Equatorial Pacific, east of the Galapagos Islands, increased during the penultimate deglaciation The supply of limiting nutrients via the Equatorial Undercurrent and atmospheric depositions were key to enhance primary productivity Global changes occurring during Heinrich Event 11 favored the arrival of nutrients to the easternmost region of the Equatorial Pacific